Bank performance in MENA region: a perspective from bank efficiency, risk-taking behaviour and market competition - Kamarudin, Fakarudin; Ali, Azlan; Haider, Jahanzaib; Qayyum, Abdul; Hussain, Hafezali Iqbal (Fundacion Aigle, 2020)
The present study was aimed at investigating the influence of risk-taking behavior on profitability for IBs in MENA region for a span of time covering 2005-19. The profitability of IBs were measured by ROA, ROE and NIM while the risk-taking behavior was identified with insolvency risk, capital risk, liquidity risk and credit risk. In addition, some controlling factors like efficiency; revenue, profit and cost efficiency and development indictors; stock market development, banking sector development and banking competition along-with macro indicators like inflation rate and GDP growth rate were used. The annual stream of data was formed in panel order by accessing the same from WDI and bank scope databases. The study uses panel data estimation like fixed, random and OLS as well as the dynamic panel estimations like GMM. The Hausman specification test and LM test were not significant which validate the use of OLS for panel estimation while Arellano-Bond, Sargan and Hansen test are not significant too which validates the GMM estimates for dynamic panel. The policy makers in IBs of MENA regions are recommended to consider ROA for measuring the profitability with greater R-square value by considering risk-taking behavior indicators like capital risk, liquidity risk and credit risk. These risk factors are taking positive capacity to strongly enhance the ROA for IBs in MENA region. The future researches may consider the comparative studies based on the variable setting of the present studies with fresh evidences. The estimated results of this study are generalizable to banking sectors only.